Measuring Track-Related Pointing Errors on the Nanshan Radio Telescope with an Optical Pointing Telescope - Ye Yuan; Zhi-Yong Liu; Na Wang (Advances in Astronomy)
The need for precise radio telescope pointing has driven great attention to investigating the effect of antenna local deformation or irregularity, such as unevenness in the azimuth track. Although the track-alidade interaction model is commonly used to investigate the pointing effect of track unevenness (such as the works on DSN 34 m antennas and the Green Bank Telescope), few experiments have been done to test the effectiveness of this model independently from the overall pointing model. To address this issue, a method utilizing an optical pointing telescope (OPT) for determining the impact of track unevenness on pointing is proposed. This method uses a group of reference pointing data collected by an OPT mounted at the bottom of the antenna alidade to extract the twist effect of the alidade from the radio telescope pointing data, thus compared with the predicted twist by the track-alidade model. This method was applied to the 26 meter Nanshan Radio Telescope (NSRT 26 m), achieving good agreement with the model-predicted values.